2014
DOI: 10.1007/s00484-014-0850-4
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the fescue toxicosis response of Bos taurus cattle

Abstract: Cattle of the same breed from different regions of the USA may have altered responses to heat stress and fescue toxicosis. Angus steers from Missouri (MO ANG, n = 10, 513.6 ± 13.6 kg BW) and Oklahoma (OK ANG, n = 10, 552.8 ± 12.0 kg BW) were fed a diet containing either endophyte-infected (E+, 30 μg ergovaline/kg BW/day) or endophyte-uninfected (E-, 0 μg ergovaline/kg BW/day) tall fescue seed for 23 days. Diet treatment began on day 2. Animals were maintained at thermoneutrality (TN, 19-22 °C, days 1-8) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…(Poole et al, 2019), heifers in the present study fed the EI diet consumed approximately 3.0 mg/d of ergovaline (approximately 7.5 µg/kg BW). Johnson et al (2015) did not observe an effect of EI (30 µg ergovaline/kg BW) on rectal temperature or maximal ST, whereas EI (5.6 µg/kg BW) increased rectal temperature, respiration rate, and ST (Eisemann et al, 2014) during heat stress in Angus steers. Al-Haidary et al (2001) observed increased rectal temperature, but no increase in ST in Herefords maintained at 31 °C and fed EI (5 µg/kg BW).…”
contrasting
confidence: 58%
“…(Poole et al, 2019), heifers in the present study fed the EI diet consumed approximately 3.0 mg/d of ergovaline (approximately 7.5 µg/kg BW). Johnson et al (2015) did not observe an effect of EI (30 µg ergovaline/kg BW) on rectal temperature or maximal ST, whereas EI (5.6 µg/kg BW) increased rectal temperature, respiration rate, and ST (Eisemann et al, 2014) during heat stress in Angus steers. Al-Haidary et al (2001) observed increased rectal temperature, but no increase in ST in Herefords maintained at 31 °C and fed EI (5 µg/kg BW).…”
contrasting
confidence: 58%
“…The production of ergot alkaloids in a number of Epichloë-infected grass species, throughout the world, is responsible for mammalian toxicoses [26]. In China, endophytic fungus-infected drunken horse grass (Achnatherum inebrians) can produce ergonovine and ergine, which can lead to livestock toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The ergot alkaloid, ergovaline is responsible for "fescue toxicosis" in livestock [24,25]. The main symptoms of fescue toxicosis are reduced feed intake, excessive salivation, reduced reproductive performance, tissue necroses of the feet and tail, and high mortality [26][27][28]. The presence of peramine is a significant deterrent to feeding for the Argentine stem weevil (Listronotus bonariensis), and is viewed as a desirable alkaloid due to its insect-resistance activity.…”
Section: Introductionmentioning
confidence: 99%